Aspergillus mural endocarditis presenting with multiple cerebral abscesses - Andrew A. Pavlina; Jared W. Peacock; Saad A. Ranginwala; Peter M. Pavlina; Joshua Ahier; Courtney R. Hanak (Journal of Cardiothoracic Surgery, 2018)
Abstract Background Fungal endocarditis is a rare and lethal cardiac infection which most commonly presents in immunocompromised patients or patients with other predisposing conditions. In a small subset of these patients, lesions present as mural masses and do not have any involvement with native valves or implanted devices. Here we present one such case which was diagnosed in the antemortem period in time to be managed with surgical resection. Case presentation A 70 year-old female patient who presented with multiple cerebral abscesses and was found on echocardiography to have a mass along the inferior wall of the left ventricle. She underwent surgical resection which revealed an Aspergillus vegetation along the left ventricle wall without any involvement of the cardiac valves. An intraoperative photograph was obtained and is presented in this case. The patient was started on antifungal therapy and expired on day 30 of treatment. Conclusions Fungal endocarditis is a rare yet lethal disease. It can be difficult to detect and workup should be initiated immediately if there is any clinical suspicion. This is especially true in any patient with predisposing conditions or any patient who presents with undiagnosed, culture-negative fevers or evidence of embolic foci. Once diagnosis is made, early initiation of antifungal therapy coupled with aggressive surgical debridement is required for any significant chance of survival.